Islamic versus conventional stock indices in Malaysia: Long-sample evidence from the FBM Hijrah Shariah Index and FBM KLCI - Ghazali, Siti Solehah; Zaharudin, Khairul Zharif; Hamzah, Farah Farhana (Journal of Islamic, Social, Economics and Development, 2025)
This paper examines the performance and information transmission between Malaysia’s main Shariah-compliant equity index, the FBM Hijrah Shariah Index, and its conventional counterpart, the FBM KLCI. Using daily data from February 2007 to October 2025, we analyse simple returns through descriptive statistics, a two-sample test of mean returns, correlation analysis, and multi-horizon Granger causality tests with 1-day, 5-day, 30-day, and 120-day lags. The results show that the two indices have very similar distributional properties: mean daily returns are statistically indistinguishable, volatility is comparable, and both series display non-normal return characteristics. Contemporaneous correlation is high and there is no evidence of systematic lead-lag effects at short horizons, while only modest bidirectional Granger causality appears at longer horizons. These findings suggest that in Malaysia Shariah screening mainly affects index composition without generating a separate risk-return regime. The study provides long-sample evidence on the integration of Islamic and conventional equity indices and offers practical guidance for benchmark selection and Shariah-based equity investment.